PENGARUH PEMBERIAN BERBAGAI DOSIS FUNGI MIKORIZA ARBUSKULAR TERHADAP PERTUMBUHAN VEGETATIF TANAMAN KEDELAI (Glycine max L. Merr.) - Dimas Fahmissidqi (Jurnal Agroekoteknologi, 2016)
The aim of the research was to determine the effect of the various dose Arbuscular Mycorrihizal fungi on the vegetative growth of soy bean plants (Glycine max L. merr) and to determine the optimal dose of Arbuscular Mycorrihizal fungi affecting the vegetative growth of soybean plants. The research was conducted in Cisonggom, Sajira districts, Parungsari village, Lebak Banten from September to December 2015. This research used Randomize Blocks Design with one factor (several dose mikoriza) with 6 level i.e. 2,5 g/polybag, 5,9 g/polybag, 7,5 g/polybag, 10 g/polybag and 12,5 g/polybag and repeated 4 times. Parameters of plants height, number of leaves, leaf area, root length, dry weight of plants, and the degree of infection of the roots were observed. The results indicated that treatment of Arbuscular Mycorrihizal fungi did not show significat effect on plant height at 1-6 week after plant, number of leaves at 1-6 week after plan, leaf area, and weight of soybeans plants. However, the provison of Arbuscular Mycorrihizal fungi showed significant effect on root length, and degree of infection of the roots with a dose of  7,5 g/polybag. Keywords: Dry land, Micoriza, Soybean